2019
DOI: 10.1080/10872981.2019.1686949
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated learning in a competency-based and flipped learning environment: learning strategies across achievement levels and years

Abstract: Background: The transition from a traditional lecture-based curriculum to a competencybased curriculum poses significant challenges to both students and faculty in medical schools, especially when the curriculum is implemented in a flipped learning environment. Self-regulated learning (SRL) has been proven to be beneficial for competency-based learning and flipped classroom learning, but medical educators cannot expect our entering medical students to bring in these learning skills automatically. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 20 publications
2
36
1
6
Order By: Relevance
“…One of our own studies looked at medical students' SRL in a flipped classroom learning environment and found that students frequently used strategies in the stages of planning and reflection, but less frequently during the learning or monitoring phase. Our study however, did not associate this with learning outcomes [17]. One study conducted in an elementary math course [9] suggested that SRL strategies in flipped learning could benefit students' construction of knowledge, and thus further improve learning achievement.…”
Section: Introductioncontrasting
confidence: 69%
See 1 more Smart Citation
“…One of our own studies looked at medical students' SRL in a flipped classroom learning environment and found that students frequently used strategies in the stages of planning and reflection, but less frequently during the learning or monitoring phase. Our study however, did not associate this with learning outcomes [17]. One study conducted in an elementary math course [9] suggested that SRL strategies in flipped learning could benefit students' construction of knowledge, and thus further improve learning achievement.…”
Section: Introductioncontrasting
confidence: 69%
“…Thus, more training and ongoing support will be needed to help students develop the SRL skills they will need to obtain the full benefits of the flipped classroom, and to help enable them to make a smooth transition from traditional lecture-focused learning [9]. For example, curriculum developers could provide concept maps or other graphic organizers to help students develop organization skills, or a learning coach could provide co-regulated learning opportunities with struggling students to share the cognitive and metacognitive thinking load [17].…”
Section: Help Seekingmentioning
confidence: 99%
“…Increasing attention is being paid to learner-centered coaching and helpful feedback as educational strategies relevant to various health education contexts [1][2][3][4]. This is consistent with the larger trending reform movement in health professions education that emphasizes self-regulation coupled to the development and practice of adaptive mastery [5][6].…”
Section: Introductionmentioning
confidence: 82%
“…Self-regulated learning strategies are used to develop self-regulated learning skills. Zheng et al (2020) revealed that students who cannot use SRL strategies may fail to understand and associate online content, which may negatively affect their performance in F2F activities. Allowing to use self-regulated learning strategies in F2F and online learning environments (OLE) while designing courses with FCM can positively contribute to students' performance (Butzler, 2016).…”
Section: Introductionmentioning
confidence: 99%